Efficient Impact Analysis of Changes in the Requirements of Manufacturing Automation Systems. Issue 3 (2015) - Teufl, Sabine; Hackenberg, Georg
Abstract: Various drivers, especially increasing market dynamics, force industrial enterprises to evolve their production facilities ever more frequently. Analyzing the impact of changed requirements on the production facilities early in the engineering process would facilitate the estimation of resulting costs and therefore reduce project risk. In industrial practice, requirements specifications are typically textual lists and only structured by a table of contents; an analysis of the impact of changes within the requirements specification is extensive, as no documented information is available about how the requirements and other elements of the requirements specification depend on each other. To identify impacts of changes in a requirements specification more efficiently, this paper proposes a model-based approach that classifies the elements of a requirements specification according to their contents and based on the classification preselects automatically candidate elements of the requirements specification that are possibly affected by the change. This paper shows the application of the approach on the manufacturing automation systems domain by means of a pick and place unit (PPU) demonstrator. The technical validation demonstrates that in the example of the PPU the impact analysis is more efficient with a content model than on an unstructured list; the effort for impact analysis is reduced further when adapting the content model to the manufacturing automation systems domain.